Relevansi Informasi Akuntansi terhadap Nilai Perusahaan: Studi Komparasi Indonesia (Local GAAP) Vs Malaysia (IFRS-NFC) - Hendrian Ian; Noorina Hartati (Jurnal Keuangan dan Perbankan, 2015)
This study aims to obtain empirical evidence about whether the effect of accounting information (operating income, operating cash flow, and book value of equity) to the firm value in Malaysia (IFRS-NFC) is stronger than the effect of accounting information (operating income, operating cash flow, and the book value of equity) to the firm value in Indonesia (Local GAAP). This study uses samples of companies in Indonesia and Malaysia. Overall, the samples obtained are 184 companies (104 companies from Indonesia and 80 companies from Malaysia) with a six-year observation period (2005-2011).This study gives an empirical evidence that the effect of accounting information book value of equity to the firm value in Malaysia (IFRS-NFC) is stronger than the effect of accounting information book value of equity to the firm value in Indonesia (Local GAAP). Control variables used are leverage.Then by looking at the significance of regression coefficients of each model, all independent variables (operating income, operating cash flow, and book value of equity) in the Malaysian model has positive effect on the dependent variable (firm value) and Indonesian model has too. But, by chow test, only coefficient book value of equity in Malaysia is higher than Indonesia model. This means that IFRS could increase the relevance of accounting information to the firm value